ANALISIS PENGARUH FINANCIAL LEVERAGE TERHADAP PROFITABILITAS PADA PT. SUBUR MEKAR ABADI KABUPATEN TAPANULI TENGAH - Febby Atika Ramadani Nasution; Safriadi Pohan; Yusi Tri Utari Panggabean (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to examine the effect of financial leverage/DER on profitability/ROE at PT.Subur Mekar Abadi. The author uses research methods in quantitative descriptive to discuss the problems faced by corporate finance. Data analysis explained the use of the results of several linear sub-data analyzes regarding financial leverage/DER on profitability/ROE (Y). The results of the study show that there is a negative relationship between financial leverage/DER and profitability/ROE at PT. Subur Mekar Abadi of 0.859, so when interpreted on a value scale it can be categorized as very strong. The regression equation obtained Y = 1.357 -0.695 X which shows the effect of financial leverage/DER on profitability/ROE at PT.Subur Mekar Abadi. The t test shows that the hypothesis proposed is rejected (not significant), where t count is -2.907 > 2.07387, which means that financial leverage/DER is not necessarily reduced by the regression coefficient/slop (0.695) if the financial leverage/DER variable is added by one unit. While the coefficient of determination is known that financial leverage/DER only plays a role of 73.8% of profitability/ROE at PT. Subur Mekar Abadi and the remaining 26.2% is influenced by other factors not included in the model.